2020
DOI: 10.1128/msystems.00542-20
|View full text |Cite
|
Sign up to set email alerts
|

Phages versus Antibiotics To Treat Infected Diabetic Wounds in a Mouse Model: a Microbiological and Microbiotic Evaluation

Abstract: Diabetes is marked by a range of complications, including chronic infections that can lead to limb amputation. The treatment of infected wounds is disrupted by arteriopathies that reduce tissue perfusion as well as by the critical development of bacterial resistance. We evaluated the impact of a local application of bacteriophages compared to that of a per os administration of amoxicillin-clavulanic acid in a mouse model of Staphylococcus aureus wound infection. We found that phage treatment resulted in improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…It is also suggested that bacteria can only resist the combination treatment by becoming avirulent, which would enable the infection to be cleared by the host's immune system and thus still achieve the desired outcome of curing the patient. Phageantibiotic synergy is thought to be caused by a mechanism whereby bacteria elongate at a cellular level due to the action of the antibiotics, promoting the replication of phages and possibly external attachment to the bacteria as it exhibits a larger surface area (Huon et al 2020). Furthermore, phageantibiotic synergy seems to work better when phages are administered before antibiotics (Pirnay et al 2021).…”
Section: Combination Therapies: Phages and Antibioticsmentioning
confidence: 99%
“…It is also suggested that bacteria can only resist the combination treatment by becoming avirulent, which would enable the infection to be cleared by the host's immune system and thus still achieve the desired outcome of curing the patient. Phageantibiotic synergy is thought to be caused by a mechanism whereby bacteria elongate at a cellular level due to the action of the antibiotics, promoting the replication of phages and possibly external attachment to the bacteria as it exhibits a larger surface area (Huon et al 2020). Furthermore, phageantibiotic synergy seems to work better when phages are administered before antibiotics (Pirnay et al 2021).…”
Section: Combination Therapies: Phages and Antibioticsmentioning
confidence: 99%
“…Having established the basic infection parameters and the lysis and stability profiles of potential new phage products in vitro , it is essential to determine their effectiveness in the context of the infection in question in vitro in order to ascertain if the anticipated efficacy can be obtained. This can be achieved through phage efficacy testing in defined polymicrobial or complex bacterial communities such as biofilms, appropriate cell lines or simulated ex vivo infection model [ 44 , 45 , 46 , 47 , 48 ]. The most informative and useful models are discussed below with an emphasis on their merits and limitations.…”
Section: Efficacy Testing In Complex In Vitro Infection Modelsmentioning
confidence: 99%
“…Phages encoding enzymes (such as depolymerase) which can chemically degrade the extracellular polymeric substances found in biofilms have been shown to be particularly useful for these purposes [ 45 ]. Importantly, phages are highly effective in pre-treatment studies at preventing biofilm formation of pathogenic bacteria associated with nosocomial, oral, urinary tract and wound infections [ 44 , 45 , 46 , 47 , 48 ]. Interestingly, phages have also been shown to be an excellent adjunct to antibiotics to clear Staphylococcus aureus in biofilm, further supporting combined phage/antibiotic therapy [ 51 ].…”
Section: Efficacy Testing In Complex In Vitro Infection Modelsmentioning
confidence: 99%
“…Although the primary host AB 2013−95 is an antibiotic-sensitive strain (Table 1), 55 of the 58 isolates are carbapenemresistant A. baumannii strains. About 6.3% of people with diabetes develop diabetic foot worldwidr, and at the infected diabetic foot ulcers, Staphylococcus aureus accounted for 42% [41], but A. baumannii is becoming one of the main bacteria in diabetic foot ulcers infections [42]. Diabetic patients suffer from shortage of tissue perfusion and limb necrosis due to microvascular disease, which obstructs the effect of active antibiotics against bacteria from chronic wound infection [41].…”
mentioning
confidence: 99%
“…About 6.3% of people with diabetes develop diabetic foot worldwidr, and at the infected diabetic foot ulcers, Staphylococcus aureus accounted for 42% [41], but A. baumannii is becoming one of the main bacteria in diabetic foot ulcers infections [42]. Diabetic patients suffer from shortage of tissue perfusion and limb necrosis due to microvascular disease, which obstructs the effect of active antibiotics against bacteria from chronic wound infection [41]. At the same time, due to the massive use of antibiotics, drugresistant bacteria develop on such wounds.…”
mentioning
confidence: 99%